Integrated Web-Based Platform for Boarding House Rental Services: Information Architecture and Booking Workflow Design - Sri Indrayani; Sintha Istikomah (Komunitas Dosen Indonesia, 2026)
Pati Regency in Central Java has experienced rapid industrial, commercial, and educational growth, attracting workers, students, and job seekers who require temporary accommodation such as boarding houses. Despite this increasing demand, the process of searching and booking boarding houses remains largely manual, relying on word of mouth, roadside banners, or direct visits, which leads to fragmented information, inaccurate room availability data, and inefficient search processes. This study aims to design and evaluate a web-based boarding house rental information system that addresses information asymmetry and fragmented search processes in local rental markets by providing structured property information and an integrated digital booking workflow. The research employs a system development approach consisting of requirements analysis through interviews and field observation, UML-based system modeling, web-based system implementation, and functional evaluation using black-box testing to verify the reliability of core system functions such as property search, availability display, booking submission, and payment confirmation. The resulting platform integrates structured property listings, multi-criteria search filters, interactive digital maps, and an online reservation mechanism that enables prospective tenants to identify, compare, and book boarding houses without physically visiting the property. Testing results indicate that all functional modules operate according to the specified requirements, supporting accurate property information retrieval and a continuous search-to-booking workflow. Beyond system implementation, the study contributes to research on digital property information systems by demonstrating how integrated information architecture and transaction workflows can reduce information fragmentation and improve transparency in temporary housing rental platforms.